Comparison of theoretical white dwarf cooling timescales. - Salaris, M. (2013)
Context. An accurate assessment of white dwarf cooling times is paramount so that white dwarf cosmochronology of Galactic populations can be put on more solid grounds. This issue is particularly relevant in view of the enhanced observational capabilities provided by the next generation of extremely large telescopes, that will offer more avenues to use white dwarfs as probes of Galactic evolution and test-beds of fundamental physics. Aims: We estimate for the first time the consistency of results obtained from independent evolutionary codes for white dwarf models with fixed mass and chemical stratification, when the same input physics is employed in the calculations. Methods: We compute and compare cooling times obtained from two independent and widely used stellar evolution codes, BaSTI and LPCODE evolutionary codes, using exactly the same input physics for 0.55 M⊙ white dwarf models with both pure carbon and uniform carbon-oxygen (50/50 mass fractions) cores, and pure hydrogen layers with mass fraction qH = 10-4MWD on top of pure helium buffers of mass qHe = 10-2MWD. Results: Using the same radiative and conductive opacities, photospheric boundary conditions, neutrino energy loss rates, and equation of state, cooling times from the two codes agree within ~2% at all luminosities, except when log (L/L⊙) > -1.5 where differences up to ~8% do appear, because of the different thermal structures of the first white dwarf converged models at the beginning of the cooling sequence. This agreement is true for both pure carbon and uniform carbon-oxygen stratification core models, and also when the release of latent heat and carbon-oxygen phase separation are considered. We have also determined quantitatively and explained the effect of varying equation of state, low-temperature radiative opacities, and electron conduction opacities in our calculations, Conclusions: We have assessed for the first time the maximum possible accuracy in the current estimates of white dwarf cooling times, resulting only from the different implementations of the stellar evolution equations and homogeneous input physics in two independent stellar evolution codes. This accuracy amounts to ~2% at luminosities lower than log (L/L⊙) ~ -1.5. This difference is smaller than the uncertainties in cooling times attributable to the present uncertainties in the white dwarf chemical stratification. Finally, we extend the scope of our work by providing tabulations of our cooling sequences and the required input physics that can be used as a comparison test of cooling times obtained from other white dwarf evolutionary codes.